“PEMBACAAN” AL-QUR’AN MENURUT MOHAMMED ARKOUN - Untung, Moh. Slamet (RELIGIA, 2010)
Ijtihad, according to Arkoun, is a law concluding process by using many exegesis techniques to understand Qur’an and Hadith. Arkoun, furthermore, said that the role of ijtihad is expanded to various more radical fields not only theology-juridical field, but also the revelation itself with Islamic rational criticism. One of the parts of Islamic rational criticism is to do historical clarification through reviewing the Quran exegesis correctly and freshly. This is done to find other meaning of the texts. In another word, to reconstruct must deconstruct the texts. Arkoun used historicism method to be applied in understanding the Quran that is how to understand the Quran critically and deeply from various different views and method from what have been done before. He viewed the Quran has uttered many interpreted texts from it that are able to fulfill many needs in certain periods after the revelation of the Quran.